Multifunctional Landscapes that Incentivize Green Innovations and Improve Livelihoods - Edward-Uwadiale, Regina (CGIAR System Organization, 2025)
This blog—the second in the Thriving Landscapes, Vibrant Futures series—explores how sustainable landscape transformation can be scaled by making it economically attractive for communities, businesses, and investors. The CGIAR Multifunctional Landscapes Science Program emphasizes aligning markets and business models with nature-positive practices to create incentives for adopting integrated landscape solutions. The article outlines efforts to co-create knowledge on market trends, develop green business opportunities, and leverage finance mechanisms such as payments for ecosystem services. It highlights practical innovations—from circular bioeconomy solutions like Black Soldier Fly farming to incubating and accelerating agroecological enterprises—that enhance livelihoods, open new economic avenues for rural communities, and provide market-driven support for biodiversity-friendly practices. By fostering inclusive value chains and financial viability, these approaches complement policy and grassroots efforts to accelerate the transition to thriving multifunctional landscapes.